Aiming High and Falling Short: California's Eighth-Grade Algebra-for-All Effort. (September 2015) - Domina, Thurston; McEachin, Andrew; Penner, Andrew; Penner, Emily
The United States is in the midst of an effort to intensify middle school mathematics curricula by enrolling more 8th graders in Algebra. California is at the forefront of this effort, and in 2008, the state moved to make Algebra the accountability benchmark test for 8th-grade mathematics. This article takes advantage of this unevenly implemented policy to understand the effects of curricular intensification in middle school mathematics. Using district-level panel data from all California K–12 public school districts, we estimate the effects of increasing 8th-grade Algebra enrollment rates on a 10th-grade mathematics achievement measure. We find that enrolling more students in advanced courses has negative average effects on students' achievement, driven by negative effects in large districts.